REALIZATION OF VISUAL TECHNIQUE DIDACTIC APPROACH IN ALGORITHMIC TRAINING OF STUDENTS THROUGH INFORMATION AND COMMUNICATION TECHNOLOGIES OF EDUCATIONAL ENVIRONMENT (Journal of Information Technologies in Education (ITE), 2016)
The article examines the development of visual learning theory, states functions of accuracy and peculiarities of visual technique realization in modern studying process, it defines the concept of “Visual learning environment” and didactic role of interactive and multimedia visualization processes. Authors examine the problem of determination of cognitive visualization potential in algorithmic training of students through information and communication technologies of educational environment.     This article specifies functions of visual aids use and implementation features of the specified principle in modern educational process and proves the didactic role of interactive multimedia visualization process that stimulates cognitive activity of student and activates perceptive mechanism of teaching information. It analyzes problem of cognitive visualization potential capacity of training of future marine personnel using informational communicative educational environment.
Keywords: visual technique; visual learning environment; information and communication educational environment; cognitive visualization; algorithmic training of navigators